(3efXheI GdYbjGf ajeG QLM GdbjGS ajg Ydi GdCSJMSGfs - (3EHQGgje GdGMSGFjs
(3ChdgG (B:s
(3GdMeO ddg GdbOje GdCHOi GdhGMO GdaQO GdcQje GdCMO hHYO jG WGdH Gdabg NP eSGFdG ajgG GdbjGS QLMhG MJekG s
(3BNQgG (B:s
(3hEf jbje TNUGf cd Efg EQJgf GdYHO ef GdPi dg aai GdbjGS GdMLJGf HWdG hHYO ehJ QGgf def jHWdkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
Keywords: (3CUhd Gdabgs